An empirical assessment of a single family-wide hybrid capture locus set at multiple evolutionary timescales in Asteraceae - Jones, Katy E; Fér, Tomáš; Schmickl, Roswitha E; Dikow, Rebecca B; Funk, Vicki A; Herrando-Moraira, Sonia; Johnston, Paul R; Kilian, Norbert; Siniscalchi, Carolina M; Susanna, Alfonso; Slovák, Marek; Thapa, Ramhari; et al. (Applications in plant sciences, 2019)
PREMISE: Hybrid capture with high-throughput sequencing (Hyb-Seq) is a powerful tool for evolutionary studies. The applicability of an Asteraceae family-specific Hyb-Seq probe set and the outcomes of different phylogenetic analyses are investigated here. METHODS: Hyb-Seq data from 112 Asteraceae samples were organized into groups at different taxonomic levels (tribe, genus, and species). For each group, data sets of non-paralogous loci were built and proportions of parsimony informative characters estimated. The impacts of analyzing alternative data sets, removing long branches, and type of analysis on tree resolution and inferred topologies were investigated in tribe Cichorieae. RESULTS: Alignments of the Asteraceae family-wide Hyb-Seq locus set were parsimony informative at all taxonomic levels. Levels of resolution and topologies inferred at shallower nodes differed depending on the locus data set and the type of analysis, and were affected by the presence of long branches. DISCUSSION: The approach used to build a Hyb-Seq locus data set influenced resolution and topologies inferred in phylogenetic analyses. Removal of long branches improved the reliability of topological inferences in maximum likelihood analyses. The Astereaceae Hyb-Seq probe set is applicable at multiple taxonomic depths, which demonstrates that probe sets do not necessarily need to be lineage-specific.
Keywords: Asteraceae; Compositae; hybrid capture; Hyb‐Seq; non‐paralogy; phylogenetics